STATUS KONFLIK DAN PERLINDUNGAN HUKUM TERHADAP KORBAN PADA KONFLIK ISLAMIC STATE OF IRAQ AND SYRIA (ISIS) DALAM PERSPEKTIF HUKUM HUMANITER INTERNASIONAL - Al Wasilah Untung Sukowati (Faculty of Law Universitas Sebelas Maret, 2015)
Conflicts involving the group Islamic State of Iraq and Syria (ISIS) is a conflict that arise in Iraq and Syria. This conflict continues to result in victims of the conflict in line with the increasing intensity of clashes in the country for territory in Iraq and Syria. International humanitarian law is a legal framework that plays an important role in determining the status of the conflict and forms of legal protection for victims of the conflict. The discussion on whether there is an armed conflict is important before determining the status of the armed conflict. After knowing the status of the armed conflict, it can be seen the provisions of international humanitarian law which is applied to protect the victims of conflict. This method uses normative law research. Source of research material used in this paper is the primary legal materials and secondary legal materials. The collection of legal materials carried with a literature study or studies document. Then, the analytical techniques legal materials used syllogism deduction.